TEACHING SOCIAL DISCIPLINES IN A POST-INDUSTRIAL SOCIETY: SPECIFICS AND TECHNOLOGY - Serebryanskiy, Yuriy; Bobinkin, Sergei; Dembitckaia, Olga; Kotova, Larisa (Revista Inclusiones, 2020)
In a post-industrial society, a creative person is formed instead of an economic person, which has prevailed for many centuries. Education in the conditions of a post-industrial society develops under the influence of both general civilizational processes and internal factors of state development and construction. The article analyzes scientific literature on the problem of the formation of a postindustrial society, post-industrial education and, in particular, teaching social disciplines in the conditions of a post-industrial society. Based on an expert survey, the advantages of using ICT in university programs of social disciplines, components of ICT competence and factors for activating educational and cognitive activities in the transition to a post-industrial society have been identified. A pedagogical experiment on the implementation of the social network "VKontakte" in the educational process when studying social disciplines has confirmed the research hypothesis that the use of ICT in the process of teaching social disciplines can become an effective means of activating cognitive and educational research activities of students and the formation of necessary skills.